PENGARUH BANTUAN RASKIN TERHADAP PENGELUARAN KONSUMEN MASYARAKAT KURANG MAMPU DI DESA ODE LUNYUK KECAMATAN LUNYUK - Ika Fitriyani; Muhammad Nur Fietroh; Delvi Ulandari; U Usman (Fakultas Ekonomi dan Manajemen, 2021)
The purpose of this study was to know the effect of giving poor rice aid (RASKIN) toward the expenditures of poor communities consumers in Lunyuk Ode Village, Lunyuk Sub-district. Type of this study was associative, namely the study aims to analyze the influence or relationship between two or more variables. The variables in this study were the giving of poor rice aids (RASKIN) as an independent variable symbolized by X and the expenditure of poor consumers as the dependent variable symbolized by Y. The data used was quantitative data in the form of respondents' answers related to the object of study collected through questionnaires. The population in this study were all poor rice recipients (RASKIN) in Lunyuk Ode Village, Lunyuk Sub-district with number of population were 69 respondent and all of them were used as samples (census sampling). Data analysis was used simple linear regression analysis techniques, hypothesis testing and determination coefficient test (R2). The results of the data analysis showed that the giving of rice aid for the poor communities (RASKIN) did not have effect toward the expenditure of consumers of the poor communities in Lunyuk Ode Village, Lunyuk Sub-district. This was indicated by the t-value of the test results of 0.038 which was lower than the t-table value at the significance level of 5% was of 1.996 (0.038<1.996). The variable ability of giving poor rice aid (RASKIN) in influencing the variation of changes in the variable expenditure of consumers of the poor village in Lunyuk Ode Village, Lunyuk Sub-district was very low, namely 1.5% while its remaining of 98.5% was influenced by other variables not included in the study.